Time Efficiency of Filling Supplies at Marine Supplies Tonda Fishing Ship in PPS Bungus, West Sumatra Province - Hafidzah, Tri Okta; Isnaniah, Isnaniah; Zain, Jonny (Journal of Coastal and Ocean Sciences, 2022)
When filling supplies at sea, it is not only troll line fishing vessels that fill up supplies at PPS Bungus but also other fishing vessels. The large number of fishing fleets filling up fishing supplies causes queues that can affect the cost of mooring ships. To find out how efficiency the time of filling supplies at sea troll line fishing vessels is and the factors that influence it, this study was conducted. The method used is a survey method of 20 sample ships that carry out fishing activities. From the results of the study, it was found that the efficiency level of filling time for troll line fishing boats ranged from 74.22% to 89.01% with an average of 82.31%, which means efficiency. The size of the efficiency level when filling fishing supplies is very dependent on the length of the effective time used. The amount of effective time is influenced by the number of supplies of clean water (x1), fuel (x2), ice cubes (x3), and the number of actors filling fishing supplies (x4), in the form of multiple regression equation Y = 58,5700 + 0.0363x1 + 0 .0488x2 + 0.1652x3 – 9.5800x4. The efficiency level of filling time for fishing supplies can still be improved by reducing wasted time